RESPONSES OF MAIZE VARIETIES TO VARYING UREA FERTILIZER REGIMES IN THE SOUTHERN GUINEA SAVANNAH AGROECOLOGICAL ZONE OF NIGERIA - Ilozobhie, Nicholas Eronmonsele; Agha, Agha U; Usman B. Ejura, Bilqis Ejura; Chorio, Philip Timothy; Azzuwut, Promise Andrew; Mohammed, Baba N. Mohammed; Sani, Adamu; Mustapha, Abdul; Aliyu, Suleiman; Ojekunle, Fatimoh; Aihebhoria, Osabhie Daniel; Okorie M. Joseph, M. Joseph (FUDMA JOURNAL OF SCIENCES, 2025)
Maize is a vital crop in Nigeria, requiring optimal plant density and good agronomic practices to achieve enhanced yields. A two-year field trial (2023-2024) was conducted at the University of Abuja’s farm in the Southern Guinea Savannah agroecological zone to evaluate maize response to varying urea application rates. A 4 × 5 factorial experiment was conducted using a Randomised Complete Block Design (RCBD) with three replications, combining four maize varieties (Sammaz-43, 44, 57, and 58) and five urea (46% N) application ranges (0, 50, 100, 150, and 200 kg/ha) with a uniform application of 45 kg/ha of phosphorus and potassium using NPK 15:15:15. Plant height, leaf count, leaf area, shelling percentage, thousand-seed weight, and grain yield were among the data collected. The results indicated that crop performance was significantly influenced by both maize cultivars and urea applications (p≤0.05). Higher urea rates improved yield parameters, with Sammaz-57 achieving top yields (3.8 t/ha in 2023 and 5.5 t/ha in 2024) with 200 kg/ha, showing unique varietal responses to urea rates. The study found a significant interaction (P≤0.05) between fertilizer application and maize variety, indicating that maize varieties responded differently to urea application. However, there was no significant difference in grain yield among the varieties, suggesting that none consistently outperformed the others across fertilizer treatments. The study recommends that farmers in the region use Sammaz-57 with 100 kg/ha urea or Sammaz-58 with 200 kg/ha urea to optimize maize growth and yield.